Actual problems of legal protection of children in the Republic of Kazakhstan - Rahimberlina, A.K.; Zhagalov, R.B. (Bulletin of the Karaganda University “Law Series”, 2018)
The article deals with the most urgent issues of state policy in the field of prevention and rehabilitation of child neglect and homelessness. The authors offer recommendations on the protection of children & apposes rights and analyze the work of the scientific and organizational center on the psychosocial needs of children and families. Moreover, the article deals with the legal protection of children left without parental care in the Republic of Kazakhstan, its forms and tasks. Kazakhstan joined the UN Convention on the Rights of the Child and follows its recommendations. The authors outline the main problems of legal protection of children in Kazakhstan and ways to solve them. Also, the lack of specialists in the regional departments for the protection of children's rights does not allow, in particular, to properly track the fate of a disadvantaged child, to reveal the reasons for a situation and to protect his rights in court. Researchers are recommended to cover all sectors of society, and especially non-governmental organizations, which play an important role in the social stabilization of Kazakhstani society to solve these issues. The cooperation of the «third sector» with the state is based on the principles of equal partnership. All this allows to monitor the observance of the rights of the child, to identify problems in establishing feedback with a wide audience, including with the media and other structures of the society working with children, including state and non-governmental organizations.